VARIABEL GURU IDEAL: SEBUAH TINJAUAN SISTEMATIS - Wahyuddin Wahyuddin (IAI DDI Polewali Mandar, 2022)
This systematic review aims to present variables that can be applied to attribute an excellent teacher. Moreover, it describes the difference of teacher criteria between the first-century (2000 and after) and pre-the-first-century (before the year of 2000). Peer-reviewed articles published in academic journals were searched on Google Scholar, Springer and Scopus by using search terms to find articles related to the systematic review purposes, which were “teacher characteristics”, “effective teacher”, “best teacher”, “teacher criteria”, “qualified teacher”, “21st century teachers”, “teacher quality” and